A eticidade hegeliana como aporte teórico para a efetivação da liberdade na democracia - Souza, Marcelo Igor da Silva e (2025)
This research, methodologically conceived in the systematics of Hegelian speculative dialectics, is primarily based on Hegel's Principles of the Philosophy of Law. Thus, it seeks to understand the limits established in the systematics of institutions in ethicality as a way of enabling the real use of practical philosophy in relation to the concept of self-conscious democracy. In this way, it seeks to demonstrate that, regardless of Hegel's advocacy of constitutional monarchy, the idea of freedom proposed in the work in question, in which the concept of free will is based on the identification of individuals' subjectivities with institutions, can be used to the extent that it enables the realization of freedom in democracy based on self-consciousness. The understanding of freedom shows that the truth of the human being is to be universal and that this only becomes possible in ethics through the state. However, this does not mean that the individual can set aside his or her particularity, since this perspective would be contrary to the dialectical process, which brings within itself the particular, the universal and the singular. The particular in the sense of recognizing individuality as an important moment of freedom, universality as the existential goal of the realization of freedom, since freedom is only realized when the individual ceases to be only “in himself” and becomes “for himself”, and the singular in the perspective that every individual is, at the same time, particular and universal. In the systematics of institutions, the dialectical relationship between them is seen as a highly relevant speculative movement, and this systematic movement is considered the foundation for the development and realization of the idea of freedom. In this sense, the research primarily addresses the concept of free will based on self-consciousness, which is considered a condition for the democratic state to be able to realize the idea of freedom in the ethical world. Finally, the essential points of the research that served as the basis for the philosophical problem of the idea of democracy are established, with the aim of emphasizing the relevance and possibility of using Hegelian thought in contemporary times.